Pest Smart interventions and their influence on farmer pest management practices in Tra Hat village, Bac Lieu Province, Vietnam - Sivapragasam, Annamalai; Le Minh Duong; Van Chien, Ho; Khing Su Li (2017)
A pre-Pest Smart (baseline) and post-Pest Smart intervention study was carried out 15 months after the baseline study was conducted to assess the influence of the Pest Smart activities on farmers’ practices, attitudes and beliefs on pest management in Tra Hat village, Bac Lieu Province, Vietnam. Farmers advocating Pest Smart activities showed favorable changes in their practices, attitudes and beliefs. Farmers reported an increase in dry yield of rice, reduced rice seeding rate (from 6.9 t/ha to 7.8 t/ha), reduced application of nitrogenous fertilizer (from 109.5 kg/ha to 93.3 kg/ha), and reduced number of insecticide sprays per season (from 3.4 times per season to 2.7 times per season). The perceived losses were also reduced significantly from 1,452 kg/ha to 718 kg/ha (reduction of 51% perceived loss of rice yield to pests).